Comparing the Nucleocapsid Proteins of Human Coronaviruses: Structure, Immunoregulation, Vaccine, and Targeted Drug - Zhang, Bo; Tian, Junjie; Zhang, Qintao; Xie, Yan; Wang, Kejia; Qiu, Shuyi; Lu, Keyu; Liu, Yang (Frontiers in Molecular Biosciences, 2022)
The seven pathogenic human coronaviruses (HCoVs) include HCoV-229E, HCoV-OC43, HCoV-NL63, and HCoV-HKU1, which usually cause mild upper respiratory tract diseases, and SARS-CoV, MERS-CoV, and SARS-CoV-2, which cause a severe acute respiratory syndrome. The nucleocapsid (N) protein, as the dominant structural protein from coronaviruses that bind to the genomic RNA, participates in various vital activities after virus invasion and will probably become a promising target for antivirus drugs design. Therefore, a comprehensive literature review of human coronavirus’ pathogenic mechanism and therapeutic strategies is necessary to the elimination of pandemic. Here, we give a systematic summary of the structures, immunoregulation, and potential vaccines and targeted drugs of the HCoVs N protein. First, we provide a general introduction to the fundamental structures and molecular function of N protein. Next, we outline the N protein mediated immune regulation and pathogenesis mechanism. Finally, we comprehensively summarize the development of potential N protein-targeted drugs and candidate vaccines to treat coronavirus disease 2019 (COVID-19). We believe this review provides insight into the virulence and transmission of SARS-CoV-2 and the support for further study on epidemic control of COVID-19.